Assessment of Dermatoglyphic Patterns in Malocclusion - Achalli, Sonika; Patla, Muralli; Nayak, Krishna; B, Ashoka; Bhat, Manohara (Journal of Dentistry Indonesia, 2018)
Dermatoglyphics is the study of fingerprints and skin patterns. Dermal configurations appear during the 12th week of intrauterine life and are completely established by the 24th week. These configurations, except the overall size, are said to remain constant throughout an individual’s lifetime. Objective: To assess the relationship between fingerprint patterns and skeletal malocclusion. Methods: Fingerprint patterns were collected using the ink method from 90 subjects who were divided into skeletal class I, II, and III malocclusion groups of 30 subjects each. Results: The loop pattern was more frequent in patients with skeletal class I and II malocclusion, and the whorl pattern was more frequent in those with class III malocclusion. Conclusion: The present study attempted to assess the relationship between dermatoglyphic patterns with skeletal malocclusion to use as an indicator of developing malocclusion at an early age.